2010
DOI: 10.1007/s12223-010-0097-3
|View full text |Cite
|
Sign up to set email alerts
|

PCR screening and sequence analysis of iol clusters in Lactobacillus casei strains isolated from koumiss

Abstract: The iol cluster (consisting of genes involved in myo-inositol utilization) was investigated in Lactobacillus casei strains isolated from koumiss. Ten strains were tested for the presence of iol cluster by PCR screening; three strains encoded this cluster. Full-sequencing procedure was conducted; the iol cluster was identical to that of L. casei BL23 (GenBank access. no. FM177140) except for an upstream transposase. The iol cluster is not a common feature for L. casei strains isolated from koumiss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Fermentation occurs naturally at ambient temperature after the addition of filtrated mare milk into the container with old koumiss, which serves as the starter culture ( Zhang and Zhang, 2011 ). Koumiss is a good source of novel bacteria of biotechnology potential ( Zhang et al, 2010a ; Pan et al, 2011 ). Therefore, it is of intense interest to explore and preserve as many fermentation-associated koumiss bacteria as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation occurs naturally at ambient temperature after the addition of filtrated mare milk into the container with old koumiss, which serves as the starter culture ( Zhang and Zhang, 2011 ). Koumiss is a good source of novel bacteria of biotechnology potential ( Zhang et al, 2010a ; Pan et al, 2011 ). Therefore, it is of intense interest to explore and preserve as many fermentation-associated koumiss bacteria as possible.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several other studies have reported high proportion of Lb. helveticus in koumiss (Uchida et al, 2007;Watanabe et al, 2008;Wu et al, 2009;Miyamoto et al, 2010;Sun et al, 2010 a;Yu et al, 2011). The reason for this difference is unclear and merits further investigations.…”
Section: Discussionmentioning
confidence: 92%
“…During the last decade, numerous studies have been conducted on the bacterial communities of traditional fermented milk products from Inner Mongolia and Mongolia (formerly Outer Mongolia), using traditional cultivation in combination with a simultaneous or subsequent differentiation of the isolates based on numerously biochemical and physiological tests or by 16S rRNA gene sequencing and characterization of potential probionts (e.g., An et al, 2004;Menghe et al, 2004;Danova et al, 2005;Batdorj et al, 2006;Shuanguan et al, 2006;Uchida et al, 2007;Watanabe et al, 2008;Guo et al, 2009;Watanabe et al, 2009;Wu et al, 2009;Bao et al, 2010;Sun et al, 2010aSun et al, , 2010bZhang et al, 2010;Yu et al, 2011). However, culture-dependent methods do not reflect the true bacteriological community, but rather the needs of different growth media for cultivation of certain bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, it was produced from the milk of horses by residents in Central Asia and China, which is one of the most important basic food products (19). There has been an increasing interest in the production of koumiss at the industrial level due to its biotechnological potential and its benefits to human nutrition and health (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%